Barriers and Motivators to Seeking Mental Health Support: An Assessment of a Southeastern Sheriff's Office - Huynh, Carol M. (Criminal justice review, 2024)
Limited research has examined what factors serve as potential barriers and motivators for law enforcement personnel in seeking mental health support. The current study presents findings from a survey of 158 sworn and civilian personnel from a large Southeastern Sheriff's office to shed light on these potential barriers/motivators. We drew on previous literature to create measures related to mental health stigma, confidentiality, burnout, various stressors, and organizational support, among others. The main effects OLS regression models suggest that increased perceptions of stigma and personal stressors significantly lowered employees’ willingness to seek mental health support. However, increased burnout and job satisfaction were associated with employees seeking mental health support. Multiplicative models show that as job satisfaction increased within nonwhite respondents, those respondents were significantly more likely to seek mental health assistance. However, as personal stressors increased among nonwhite respondents, those respondents were significantly less likely to seek help. Finally, as overall health increased among white respondents, those respondents were significantly more likely to seek help. Findings indicate that mental health issues experienced by employees vary based on group membership. We discuss several future research directions and policy implications derived from these findings.